PERANCANGAN SISTEM TRANSMISI GOKAR LISTRIK - Jerry Rapar Pangayow; Stenly Tangkuman; Michael E Rembet (JURNAL POROS TEKNIK MESIN UNSRAT, 2016)
The Development of automotive todays is very fast because every single year there is always something new. This research aims to design fuel-efficient vehicles and environmentally friendly, especially the transmission is driven by an electric motor that used a chain sprocket transmission system is applied to the electric gocart. From the results of this research shows that the transmission can be used on a simple electric gocart transmission system chain sprocket is roll type single line, which consists of two sprocket and chain on rotation 1 750 rpm and 2 hp motor power. Dimensions obtained by the small sprocket diameter 35 mm with a number of teeth 9 pieces, large sprocket diameter 250 mm with a number of teeth 62 fruit and chain length of 1,243 mm at a distance of 381 mm spindle axis. Keywords: Design, Transmission Chain, Electric Gocart